NON-INTERVENTION PRINCIPLE, HUMAN RIGHTS VIOLATIONS AGAINST ETHNIC ROHINGYA, AND INDONESIA'S ROLE IN THE UN HUMAN RIGHTS COUNCIL - Maghfirah, Alya; Tinianus, Enzus (Universitas Syiah Kuala, 2024)
Article 2, Paragraph 2(e) of the ASEAN Charter stipulates the principle of non-interference in the internal affairs of ASEAN Member States, which serves as the foundation for the non-intervention policy within the organization. Unfortunately, this principle has had a detrimental effect on ASEANs ability to address human rights violations against the Rohingya ethnic minority in Myanmar. The goal of this thesis is to evaluate the applicability of the non-intervention principle within ASEAN and to analyze Indonesia's role as a member of the UN Human Rights Council in addressing these human rights violations. This research employs a normative juridical method with qualitative analysis. The findings indicate that the current strict adherence to the non-intervention principle within ASEAN needs to be reformed, as it obstructs potential solutions to the human rights issues faced by the Rohingya. On the other hand, Indonesia, serving as a member of the UN Human Rights Council, has made significant diplomatic efforts to address the situation, including establishing refugee camps for ethnic Rohingya within its territory.